THE LIBERAL ASPECTS OF COOPERATION IN CHINA-INDIA RELATIONS - Tehseena Nazir; Shazia Nazir (RADJA PUBLIKA, 2024)
The China-India relationship has evolved significantly since the mid-20th century, propelled by their emergence as key economic powers and their shared historical legacies as ancient civilizations. This paper explores the liberal aspects of their economic cooperation, investigating how economic liberalization has reshaped and deepened their bilateral relations. China's economic reforms in the late 1970s and India's liberalization policies from the 1980s onwards have been instrumental in fostering a framework of economic engagement between the two nations. This liberal aspect manifests through the dismantling of trade barriers, promotion of inclusive economic policies, and facilitation of mutually beneficial investments and technological collaborations. Despite occasional geopolitical tensions and historical territorial disputes, both countries have actively pursued political cooperation in global forums like the G20 and BRICS, advocating for inclusive growth and sustainable development. Cultural exchanges further strengthen ties, fostering mutual understanding and enriching the cultural fabric of both nations. This paper underscores how the liberalization-driven economic partnership between China and India serves as a foundation for broader cooperation, influencing regional stability and global economic governance in the 21st century.